DOI: 10.58837/chula.the.2019.239
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of adzuki bean vigna angularis hydrolysate by alginate-based beads

Thasanporn Sangsukiam

Abstract: The aims of this research were to study the effect of different cooking conditions on bioactive compounds and biological activities of cooked adzuki beans and cooking water. The different encapsulation methods to entrap adzuki beans hydrolysate were investigated. The release characteristics of different freeze-dried alginate particles were investigated after�in vitro�simulated gastrointestinal digestion. The results showed that all cooking conditions (60-min boiling, 10-min autoclaving and 60-min autoclaving) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…The chia seed protein hydrolysates obtained in this study showed signi cantly enhanced functional antioxidant activities, suggesting that they may affect the molecular structure, hindering their ability to serve as electron donors [28]. Although DPPH activity reached its highest value and remained stable after 2 h of hydrolysis, ABTS activity continued to increase until 6-hour hydrolysis which is similar to the results of Sangsukiam et al (2019)[48], as shown in Fig. 4B.…”
Section: Isolation Of Chia Seeds Protein Hydrolysate By Crude Proteas...supporting
confidence: 82%
“…The chia seed protein hydrolysates obtained in this study showed signi cantly enhanced functional antioxidant activities, suggesting that they may affect the molecular structure, hindering their ability to serve as electron donors [28]. Although DPPH activity reached its highest value and remained stable after 2 h of hydrolysis, ABTS activity continued to increase until 6-hour hydrolysis which is similar to the results of Sangsukiam et al (2019)[48], as shown in Fig. 4B.…”
Section: Isolation Of Chia Seeds Protein Hydrolysate By Crude Proteas...supporting
confidence: 82%